Pengembangan Lembar Kegiatan Peserta Didik (LKPD) Berbasis Online Pada Materi Asset Tetap di SMKN 6 Surabaya - Ailin Utami Rachmania; Agung Listiadi (Jurnal Pendidikan Akuntansi (JPAK), 2022)
With the provision of this research which aims to develop student worksheets by applying an online basis to the application of materials, recording, and application of assets at SMKN 6 Surabaya, the analysis will be in accordance with this e-LKPD based on the assessments of several experts and responses from participants regarding LKPD. - this LKPD. Model development with 4-D from Thiagarajan. The stages achieved in developing the LKPD are define, design, and develop. In collecting data through study sheets, validation sheets, and student questionnaires. Testing this media on 20 students of class XII Financial Accounting and Institutions 1 SMKN 6 Surabaya. Referring to the results of repeated studies that LKPD is said to be very feasible with the overall average value of the components, namely 84.62%. The value is limited to content, presentation, language and graphics. And for the student's response, the percentage is 97.2% with a very understanding category, this proves that students give a positive response. Based on the results of this product, that the developed LKPD is very suitable to be used as teaching material.